2020
DOI: 10.1590/1808-1657000782018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of insecticides in control of Diatraea saccharalis (Lepidoptera: Crambidae) in sugarcane

Abstract: The population of the caterpillar Diatraea saccharalis (Lepidoptera: Crambidae) has increased in the crop of sugarcane in recent years. Although the control of this insect is traditionally carried out through biological control, the use of phytosanitary products has still been necessary. Therefore, the goal of this work was to evaluate the performance of different insecticides in sugarcane borer control, as well as the effect on productivity and total recoverable sugar (TRS). The experiment was conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The concomitant use of parasitoids with chemical insecticides can affect T. galloi emergence and survival, and hence reduce its population in the field (Cônsoli et al, 2008; Costa et al, 2014). The insecticidal molecule chlorantraniliprole, for example, has high control rates for D. saccharalis infestations (Silva et al, 2020), causing irregular contraction of muscle cells, leading to paralysis, lethargy, starvation, and death (Tohnishi et al, 2005). However, studies have demonstrated the negative effects of chemical insecticides on natural enemies, such as parasitoids used in sugarcane (Desneux et al, 2007; Goulart et al, 2012; Costa et al, 2014; Beloti et al, 2018; Matioli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The concomitant use of parasitoids with chemical insecticides can affect T. galloi emergence and survival, and hence reduce its population in the field (Cônsoli et al, 2008; Costa et al, 2014). The insecticidal molecule chlorantraniliprole, for example, has high control rates for D. saccharalis infestations (Silva et al, 2020), causing irregular contraction of muscle cells, leading to paralysis, lethargy, starvation, and death (Tohnishi et al, 2005). However, studies have demonstrated the negative effects of chemical insecticides on natural enemies, such as parasitoids used in sugarcane (Desneux et al, 2007; Goulart et al, 2012; Costa et al, 2014; Beloti et al, 2018; Matioli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%